Molecular cloning, spatial and temporal expression analysis of CatSper genes in the Chinese Meishan pigs - Li Bichun; Wang Xiaoyan; Xie Yuxiu; Wu Han; Gao Bo; Song Chengyi; Chen Guohong; Mao Jiude (BMC, 2011)
Abstract Background Sperm ion channel proteins (CatSpers) are essential for sperm hyperactivated motility, and then penetration through the zona pellucida. The CatSper class of proteins have well been characterized in the mouse and human. However, such data for pigs are not available. In the present study, we cloned the porcine CatSper 1-4 genes, analysed their spatial expression in various organs and temporal expression in the testes from birth until sexual maturity in Meishan boars. Methods Rapid amplification of cDNA ends (RACE) was performed to clone the full length cDNAs of porcine CatSper genes and bioinformatics analysis of inferred CatSper proteins was also determined. Various organs were collected from 150 day-old pigs to characterize the spatial expression of CatSper genes by qualitative reverse transcriptase polymerase chain reaction (RT-PCR), and testes from birth to 150 day-old boars were sampled to detect the temporal expression of CatSper genes by quantitative real-time RT-PCR. Results The mRNA sequences of CatSper1 (2452 bp), CatSper2 (2038 bp), CatSper3 (1408 bp), and CatSper4 (1799 bp), including full length of cDNAs, 5' and 3' flanks, were obtained. The bioinformatics analysis indicated that coding regions spanning the ion transport domains were conserved for different species analyzed. Among the four CatSpers, CatSper2, 3, and 4 were more conserved across species, compared with CatSper1. In addition, six conservative trans-membrane domains, a pore forming motif, and a coiled-coil motif were also identified. The spatial analysis from different organs showed that CatSper1 was detected in both testes and hypothalamus, CatSper2 was restricted in testes only, CatSper4 was expressed in testes and rete testes; whereas CatSper3 was more ubiquitously. CatSper3 and CatSper4 transcripts were also detected in ejaculated sperm. At Days 1 and 30 of age, CatSper mRNAs exhibited only sparse expression in the testes. However, these transcripts highly expressed at Day 60 and onward till sexual maturity (Day 150 of age). Conclusions The spatial and temporal expression profiles of CatSper genes were reported herein for the first time in pigs. CatSper1, CatSper2 and CatSper4 were primarily expressed in testes, while CatSper3 transcript was prevalent in a variety of organs. CatSper3 and CatSper4 mRNAs were present in mature sperm cells. Substantial upregulation of CatSper genes was initiated at Day 60 and maintained this marked production until sexual maturity.